Exposure to violent crime, fear of crime, and traumatic stress symptomatology. - Engelbrecht, Sarah-Kate (My University, 2011)
The central aim of the study was to investigate the relationships between exposure to violent crime, traumatic stress symptomatology, and fear of crime. Secondary areas of interest included the effect of the frequency of exposure to violent crime on traumatic stress symptomatology and fear of crime, as well as sex differences in the three main variables of study. In order to explore these aims, a quantitative cross-sectional research design was used. Measures included a self-developed exposure measure, the Impact of Event Scale-Revised, and a fear of crime measure used in a previous South African study. The sample was comprised of 216 first-year university students at the University of the Witwatersrand in Johannesburg. Statistical analyses included descriptive statistics, Pearson’s correlations, t-tests, and analysis of variance (one-way and two-way) and post-hoc t-tests. The results of the research indicated high levels of exposure to violent crime (including direct and indirect exposure). Almost half the sample (47%) reported exposure to violent crime in the preceding 12 months. Furthermore, over half the sample (58%) reported direct exposure to non-crime trauma in the preceding 12 months, with only about one-quarter of the sample (20%) reporting no exposure to any kind of trauma in the preceding 12 months. It was thus unsurprising that levels of traumatic stress symptomatology were generally in the moderate range and at least 20% of the total sample reported traumatic stress symptomatology of clinical concern. Fear of crime was found to be rather pervasive in the sample. Findings showed support for the relationships between exposure to violent crime and traumatic stress symptomatology, exposure to violent crime and fear of crime, and fear of crime and traumatic stress symptomatology. Significant differences were found between groups based on level and type of exposure and significant correlations were found between the perceived severity of exposure to violent crime on the one hand, and traumatic stress symptomatology and fear of crime on the other hand. Frequency of exposure to violent crime was found to be significantly related to fear of crime but not to traumatic stress symptomatology. Female subjects reported significantly higher perceived severity of exposure to violent crime, hyperarousal related symptoms and fear of crime. The implications of the findings are explored.